Empowering Society to Support Creative Economy by Stocking Flower Craft in Sumber Rejo Village Umbulsari Subdistrict - Firdha Kusuma Ayu Anggraeni; Lailatul Nuraini (LP2M Universitas Jember, 2022)
Creating stocking flower craft in Sumber Rejo Village is an activity to support creative economy and empower society. A creative economy is an activity to create added value based on ideas that come from the creativity of human resources and are based on science, cultural heritage, and technology. The handicraft sector is one sector that can be developed. The partner of the executor is the PKK (The Indonesian Family Welfare Guidance) in Sumber Rejo Village, Umbulsari District, Jember Regency, has a creative idea by using stockings to turn them into beautiful flower-shaped crafts. The partner problem that will be resolved by the proposing team is to provide training on online digital-based marketing plans and strategies with the hope of being able to increase a broad market share and increase sales turnover. Besides that, it also carries out product development by forming flowers in a bouquet and placing it in a frame as a wall decoration. Based on the implementation of community service to partners in the Sumber Rejo Umbulsari area of ​​Jember, it can be concluded that there has been an increase in knowledge and abilities about stocking flower creation, increased abilities regarding the use of online media as a media for marketing products, and strategies in marketing online.